Squamous cell carcinoma arising from chronic lymphedema: case report and review of the literature - Carlos Augusto Gomes; Camila Beatriz Silva Magalhães; Cleber Soares Junior; Rodrigo de Oliveira Peixoto (São Paulo Medical Journal)
CONTEXT: Squamous cell carcinoma arising from chronic lymphedema has only been reported in the literature 11 times (12 cases). Some aspects of its pathogenesis remain unclear and, for the first time, attention has been drawn to epidemiological data. CASE REPORT: A 90-year-old white female with chronic unilateral lower-limb lymphedema, secondary to trauma 20 years earlier, presented with a three-month history of a vegetating cutaneous lesion. There had not been any previous local ulceration. The tumor was completely excised and the histopathological analysis showed that it was an infiltrating squamous cell carcinoma. A literature review in the Medline (Medical Literature Analysis and Retrieval System Online) and Lilacs (Literatura Latino-Americana e do Caribe em Ciências da Saúde) databases using the MeSH (Medical Subject Heading) terms "Carcinoma, Squamous Cell" AND "Lymphedema" identified 112 references and found 12 similar case reports.